2006
DOI: 10.4049/jimmunol.177.4.2340
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic Lymphoid Chemokines Synergize with Adhesion Ligands to Trigger T and B Lymphocyte Chemokinesis

Abstract: Homeostatic chemokines such as CCL19, CCL21, and CXCL13 are known to elicit chemotaxis from naive T and B cells and play a critical role in lymphocyte homing to appropriate zones within secondary lymphoid organs (SLO). Here we tested whether CCL21 and CXCL13 modulate murine lymphocyte motility in the absence of concentration gradients, using videomicroscopy to directly observe the migration of single cells. CCL21 treatment of T cells induced rapid polarization and sustained random migration with average speeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 52 publications
3
79
0
Order By: Relevance
“…It is possible that signaling through SLC binding to CCR7 requires synergism with signaling events from other pathways to induce an optimal response. Indeed, previous reports have demonstrated that SLC can synergize with other adhesion molecules such as ICAM-1 and VCAM-1 to promote chemokinesis of lymphocytes during in vitro assays (57). Therefore, the finding that L-selectin-mediated enhancement in chemotaxis was specific for SLC and not ELC may be due to the inherent differences in intracellular signaling events triggered by the binding of these two chemokines to CCR7.…”
Section: Discussionmentioning
confidence: 51%
“…It is possible that signaling through SLC binding to CCR7 requires synergism with signaling events from other pathways to induce an optimal response. Indeed, previous reports have demonstrated that SLC can synergize with other adhesion molecules such as ICAM-1 and VCAM-1 to promote chemokinesis of lymphocytes during in vitro assays (57). Therefore, the finding that L-selectin-mediated enhancement in chemotaxis was specific for SLC and not ELC may be due to the inherent differences in intracellular signaling events triggered by the binding of these two chemokines to CCR7.…”
Section: Discussionmentioning
confidence: 51%
“…Because CCR7 signaling can increase motility in T cells (15) and in some cases DCs in 2D culture (34,35), we next examined the influence of CCL19 and CCL21 on DC motility in a 3D environment both in terms of activating cells to be motile as well as affecting their average (random) speed. We found that in 3D, chemokinetic effects on DCs were relatively small (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the positively charged C terminus of CCL21 gives it strong binding affinity to a wide range of proteoglycans [as well as type IV collagen (10)], unlike CCL19 (11)(12)(13). Additionally, matrix-bound CCL21 can activate DC and T cell adhesion to adhesion ligands like ICAM-1 (14,15). This study addresses the question of how DCs respond to gradients of CCR7 ligands in 3D environments-in particular, whether they differentiate between soluble vs. matrix-bound signals, and the relative importance of gradient steepness vs. average concentration.…”
mentioning
confidence: 99%
“…The efficacy of CCR7 ligands in promoting chemokinesis (this study and Refs. 26,32) suggests that CCR7 may be especially adapted for promoting and maintaining cell motility for prolonged periods. We speculate that CXCR5 is similarly adapted for promoting prolonged B cell motility within lymphoid follicles.…”
Section: Discussionmentioning
confidence: 99%